2021
DOI: 10.1155/2021/5709257
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Glaucoma Segmentation and Classification Strategies Using Depth Optimized Machine Learning Strategies

Abstract: Glaucoma is a major threatening cause, in which it affects the optical nerve to lead to a permanent blindness to individuals. The major causes of Glaucoma are high pressure to eyes, family history, irregular sleeping habits, and so on. These kinds of causes lead to Glaucoma easily, and the effect of such disease leads to heavy damage to the internal optic nervous system and the affected person will get permanent blindness within few months. The major problem with this disease is that it is incurable; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…An analysis revealed that medical T phase and preoperative axillary ultrasound outcomes have been related to ALN condition in patients with newly diagnosed breast cancer, but the diagnostic effectiveness of axillary ultrasound to evaluate ALN condition was poor in such a region [ 16 ]. Radiology could automatically extract a huge number of quality image attributes from clinical images that are difficult to recognize with the human eye [ 17 ]. Machine learning approaches have been increasingly employed in prediction in the current year, particularly in medical assessment [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis revealed that medical T phase and preoperative axillary ultrasound outcomes have been related to ALN condition in patients with newly diagnosed breast cancer, but the diagnostic effectiveness of axillary ultrasound to evaluate ALN condition was poor in such a region [ 16 ]. Radiology could automatically extract a huge number of quality image attributes from clinical images that are difficult to recognize with the human eye [ 17 ]. Machine learning approaches have been increasingly employed in prediction in the current year, particularly in medical assessment [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regular screenings for pathological diseases of the retinal [ 3 , 4 ] could greatly aid in the avoidance of vision blindness. The most extensively utilized technique for earlier screenings and identification of disorders that cause blindness including diabetic retinopathy, age-related macular degeneration, glaucoma [ 5 ], stroke-induced, and hypertension alterations is fundus photography [ 6 ]. With the advancement of film-dependent photographic cameras to electronically imaging detectors, and also angiography, red-free imaging, hyperspectral imaging, stereo photography, and other techniques, fundus imaging has vastly enhanced, lowering inter as well as intraobserver reported variation.…”
Section: Introductionmentioning
confidence: 99%
“…Uropathogens first attach to and populate related to the local of a proximal urethra via the ascending route as in Figure 1 . Individuals with staining from around the lower abdomen, patients having urinary catheters, or females who take spermicidal drugs have a harder time enhancing this channel [ 6 ]. Up to 50% of illnesses in individuals with established cystitis could ascent through into higher urinary tracts, and also, the majority of instances of pyelonephritis were associated with increased morbidity ascending from the bladder over all the ureter and then into the renal pelvis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%